THE ADVANCE OF TECHNOLOGICAL AND SUSTAINABLE INNOVATIONS IN BRAZILIAN FINANCIAL INSTITUTIONS: AN INTEGRATIVE LITERATURE REVIEW (CIPEEX, 2025)
The Brazilian financial landscape is undergoing a number of changes, all due to the incorporation of sustainable technologies and practices. These innovations are revolutionizing the way financial institutions operate, provide services and communicate with their clients. In Brazil, this movement is growing stronger, driven by several factors, including the increased search for sustainable investments, stricter regulations and greater recognition by companies of their social and environmental responsibility. This study aims to examine the progress of technological innovations and sustainable development in Brazilian financial institutions, along with their possible future directions, through an integrative literature review. The information for the research was gathered from the SciELO and CAPES Periodicals Portal databases, using the search terms "Financial Innovations", "Green Finance" and "Financial Technology". We selected articles published between 2020 and 2024, which had an ISSN with a quality level equal to or higher than B2 on the Sucupira Platform, and which addressed the topics comprehensively. Articles that duplicated or diverged from the theme of the dissertation were excluded from the menu, resulting in the use of 05 articles for analysis. The analysis of these studies shows that innovation in the banking sector not only expands access to financial services through digital platforms, but also provides a more effective, personalized and secure banking experience for customers. Financial institutions benefit from implementing environmental practices, such as mitigating the risks associated with climate change, improving the company's reputation and attracting investors and consumers concerned about environmental sustainability. These innovations strengthen sustainability in the financial sphere and meet the growing demand for responsible and ethical investments from conscious consumers and investors. In conclusion, in order for technological and sustainable innovations to have a real impact, it is essential to maintain a constant commitment to education, transparency and cooperation with various stakeholders in the development of evaluation and search methodologies that bring more solid methods and results, which foster education and studies within this area. Through this collaboration, Brazil's financial institutions have the opportunity not only to follow, but also to lead the global change towards a more sustainable and fair future, with a more solid financial system that not only drives economic growth, but also stimulates social and environmental well-being within the monetary landscape.
Keywords: financial institution; financial technology; green finance; sustainable innovations